Effects of nasal corticosteroids on boosts of systemic allergen-specific IgE production induced by nasal allergen exposure. - Cornelia Egger; Christian Lupinek; Robin Ristl; Patrick Lemell; Friedrich Horak; Petra Zieglmayer; Susanne Spitzauer; Rudolf Valenta; Verena Niederberger (PLoS ONE)
Background Allergen exposure via the respiratory tract and in particular via the nasal mucosa boosts systemic allergen-specific IgE production. Intranasal corticosteroids (INCS) represent a first line treatment of allergic rhinitis but their effects on this boost of allergen-specific IgE production are unclear. Aim Here we aimed to determine in a double-blind, placebo-controlled study whether therapeutic doses of an INCS preparation, i.e., nasal fluticasone propionate, have effects on boosts of allergen-specific IgE following nasal allergen exposure. Methods Subjects (n = 48) suffering from grass and birch pollen allergy were treated with daily fluticasone propionate or placebo nasal spray for four weeks. After two weeks of treatment, subjects underwent nasal provocation with either birch pollen allergen Bet v 1 or grass pollen allergen Phl p 5. Bet v 1 and Phl p 5-specific IgE, IgG1-4, IgM and IgA levels were measured in serum samples obtained at the time of provocation and one, two, four, six and eight weeks thereafter. Results Nasal allergen provocation induced a median increase to 141.1% of serum IgE levels to allergens used for provocation but not to control allergens 4 weeks after provocation. There were no significant differences regarding the boosts of allergen-specific IgE between INCS- and placebo-treated subjects. Conclusion In conclusion, the application of fluticasone propionate had no significant effects on the boosts of systemic allergen-specific IgE production following nasal allergen exposure. Trial registration http://clinicaltrials.gov/NCT00755066.